Contact Calls Facilitate Group Contraction in Free-Ranging Goats (Capra aegagrus hircus) - O'Bryan, Lisa R.; Abaid, Nicole; Nakayama, Shinnosuke; Dey, Tanujit; King, Andrew J.; Cowlishaw, Guy; Rubenstein, Daniel I.; Garnier, Simon (Frontiers in Ecology and Evolution, 2019)
Many social animal species produce vocalizations believed to facilitate group contraction when one or more group members have become distant. However, the mechanisms underlying this function remain unclear for many species. We examined this question with data on a semi-free ranging group of 16 adult domesticated goats (Capra aegagrus hircus) inhabiting Tsaobis Nature Park, Namibia. All goats wore dataloggers consisting of a GPS and audio recorder for 5-6 hours per day for 10 days, providing continuous data on their geolocations and vocal communication. We found that callers were farther from the group centroid than expected by chance and that call production was associated with the cessation of group expansion and subsequent group contraction. We did not find strong evidence for antiphonal call exchange between distant and core group members. Rather, we found that (i) call production by distant group members is associated with a significant reduction of group movement away from the caller, and (ii) call production by core group members is associated with greater, though not significantly greater, group movement towards the caller. These findings suggest that calls may be used by distant, and potentially core, group members to facilitate the contraction of group spread. Results from our study clarify the mechanisms through which social animals can regulate collective movement behavior and the specific role that vocalizations play in this process.